Pengaruh Pendekatan Solution Focused Brief Counseling terhadap Resiliensi Akademik Siswa Kelas VII MTs Miftahul Arifin Lumajang - Eka Permatasari, Intan Kumala; Budiono, Arifin Nur; Karamoy, Yurike Kinanthy (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2025)
This study aims to identify the effects of the implementation of SFBC on the academic resilience of seventh-grade students at MTs Miftahul Arifin Lumajang in the 2022/2023 academic year. A total of 14 students were purposively selected from a total population of 141 students as study subjects. Data were obtained using questionnaires and documentation studies, using an academic resilience scale questionnaire. The output of the data collection process and data processing were carried out to apply the Wilcoxon Signed Rank Test and the Mann-Whitney Test using SPSS version 25 software. Academic resilience refers to an individual's capacity to face and overcome various challenges in the educational environment, where perseverance is one of the main indicators. Based on the results of the analysis, a significance value of Asymp.Sig. of 0.018 was obtained in the Wilcoxon Test and 0.003 in the Mann-Whitney Test. Based on the provision that the null hypothesis (H0) is rejected if the Asymp.Sig. value is below 0.05, the results of the analysis support the acceptance of the alternative hypothesis (Ha). Thus, this study concludes the following: first, there was a significant change in the students' condition between before and after treatment, indicating an improvement after they participated in group counseling services using the scaling question technique. Second, the SFBC approach through group counseling with the scaling question technique was proven to have a positive impact on increasing the academic resilience of seventh grade students at MTs Miftahul Arifin Lumajang.